The Distribution of MAP-2 Phosphorylation in Cerebral Cortex of Long-Tailed Monkey Fetuses (Macaca fascicularis) in the Last Trimester of Gestation - Pangestiningsih, Tri Wahyu; Irawan, Vidya; Sulistiawati, Erni (Indonesian Journal of Biotechnology, 2010)
Memories are storage in cholinoceptive cells, the cells which are enriched with microtubule-associated protein 2 (MAP-2) that localized in the neuronal dendrite and the cell bodies. Phosphorylation of MAP-2 may increase memory with reduce stability of dendrite by altered dendrite length and lead new side-branches of neuronal as a neuronal plasticity processes in cerebral cortex. The aim of this research is to study the distribution of MAP-2 phosphorylation neurons in cerebral cortex of long-tailed macaques in the third semester of gestationalimmunohistochemically using avidin biotin conjugated complex method. Neurons MAP-2 phosphorylation immunoreactive were located in dendrites and cell bodies, mostly in pyramidal neurons of cerebral cortex. Intensity of MAP-2 phosphorylation immunoreactivity in layer V were stronger than another layer and the neurons that very intensely stained were the pyramidal cells in frontal and parietal lobes, that was suggested that neurons in this areas more responsive to neuroplasticity. From the results we concluded that MAP-2 phosphorylation already distributed in the cerebral cortex of long-tailed macaque fetuses at the last trimester of gestation, mostly in the pyramidal cells of layer V that is suggested plays a role for preparation of memoryformation.Keywords: fetus, long-tailed monkey, cerebral cortex, memory, MAP-2 phosphorylation